Fast screening method to characterize lithium ion battery electrolytes by means of solid phase microextraction – gas chromatography – mass spectrometry. Issue 74 (5th October 2017) - Horsthemke, Fabian; Friesen, Alex; Mönnighoff, Xaver; Stenzel, Yannick P.; Grützke, Martin; Andersson, Jan T.; Winter, Martin; Nowak, Sascha
Abstract : Several electrolytes of commercially available lithium ion batteries (LIBs) were analyzed by solid phase microextraction – gas chromatography – mass spectrometry (SPME-GC-MS). Abstract : Several electrolytes of commercially available lithium ion batteries (LIBs) were analyzed by solid phase microextraction – gas chromatography – mass spectrometry (SPME-GC-MS). The uptake and subsequent injection of the conducting salt LiPF6 into the GC system was prevented by using a headspace SPME setup. Thus, a removal step prior to the GC-MS measurements was not necessary and it was possible to analyze the untreated electrolyte without injecting the hazardous LiPF6 into the GC system. Furthermore, all SPME experiments were carried out at room temperature to exclude further thermal alteration of the electrolyte during sampling. In LIB electrolytes, different linear and cyclic carbonate solvents and additives such as succinonitrile (SN) and fluoroethylene carbonate (FEC) could be identified using the SPME-GC-MS setup. Moreover, the aging products dimethyl-2, 5-dioxahexane dicarboxylate (DMDOHC) and ethylmethyl-2, 5-dioxahexane dicarboxylate (EMDOHC) were identified in the electrolyte of aged 18 650-type cells. In the case of the cells of one specific supplier, various additional hydrocarbons were detected via SPME-GC-MS. These compounds could not be obtained when a GC-MS setup with conventional liquid or headspace injection is used. Consecutive experiments were carried out by extracting the electrolyte components directly from the headspace above anode, separator and cathode of an aged 18 650-type cell, which confirmed the findings of the prior analysis of pure electrolytes. Within this work it was possible to develop a method for the investigation of LIB electrolytes and their decomposition products with high sensitivity and low GC column bleeding.